2020
DOI: 10.1080/07853890.2020.1831050
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and viral infections and related inflammatory responses in chronic obstructive pulmonary disease

Abstract: In COPD patients, bacterial and viral infections play a relevant role in worsening lung function and, therefore, favor disease progression. The inflammatory response to lung infections may become a specific indication of the bacterial and viral infections. We here review data on the bacterial-viral infections and related airways and lung parenchyma inflammation in stable and exacerbated COPD, focusing our attention on the prevalent molecular pathways in these different clinical conditions. The roles of macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 148 publications
(211 reference statements)
3
27
0
1
Order By: Relevance
“…Statistics are important, whether from administrative data, surveys or controlled studies. Asthma and other chronic obstructive lung diseases are silent killers; therefore information pertaining these diseases is important to guide decision making for quality health service provision (D'Anna et al 2021;Shayo and Bintabara 2019;Sharma et al 2018). In this study, we have tested for region and tted a related prediction model for ACOLD incidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics are important, whether from administrative data, surveys or controlled studies. Asthma and other chronic obstructive lung diseases are silent killers; therefore information pertaining these diseases is important to guide decision making for quality health service provision (D'Anna et al 2021;Shayo and Bintabara 2019;Sharma et al 2018). In this study, we have tested for region and tted a related prediction model for ACOLD incidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Open access and increase airway inflammation. [5][6][7] It has been found that 40%-55% of COPD exacerbations are associated with bacterial infections. 8 9 COPD flare-ups caused by bacterial infections are characterised by a more severe airway and systemic inflammation responses compared with those caused by non-bacterial infections.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, mechanisms causing asthma exacerbations are still not fully understood and are different among children [ 77 , 78 ]. Hence, a better comprehension of the underlying pathogenic processes could lead to further treatment options [ 78 , 79 ].…”
Section: Anelloviruses and Chronic Respiratory Diseasesmentioning
confidence: 99%
“…However, mechanisms causing asthma exacerbations are still not fully understood and are different among children [ 77 , 78 ]. Hence, a better comprehension of the underlying pathogenic processes could lead to further treatment options [ 78 , 79 ]. The introduction of non-culture-based methods (i.e., next-generation sequencing technologies) has yielded the detection of previously unknown human pathogens [ 80 , 81 ], leading to better investigating the host–microbiome interactions and specifically the part of the virome in lung diseases [ 80 ].…”
Section: Anelloviruses and Chronic Respiratory Diseasesmentioning
confidence: 99%